Risk factors associated with Theileria parva infection in cattle in smallholder dairy farms in Muranga District, Kenya. A longitudinal study - Gitau, G.K.; Perry, Brian D.; McDermott, John J.; Katende, J.M.; Maribei, J.M. (1997)
In Kenya, the vast majority of dairy farms are owned and run by smallholder farmers. These farms are estimated to produce 75-90 percent of the milk sold in Kenya (Mbogoh, 1984a, b); about 65 percent of dairy cattle in the smallholder farms are stall-fed for the greater part of the year (Gitau et al., 1994). Dairy farming provides an income through the sale of milk and meat and tends to be a more consistent source of income than many other farming enterprises, in the medium to high potential farming areas. A number of factors limit the further Development of the dairy industry, including diseases, poor management, inadequate nutrition and lack of farm inputs (Goldson and Ndeda, 1985). Among the diseases, tick-borne infections, in particular East Coast fever (ECF) caused by Theileria parva and transmitted by the tick Rhipicephalus appendiculatus, are the most important. A one and a half year longitudinal study was conducted in Murang'a District to estimate the incidence of T. parva infections among the smallholder dairy farms. Three agroecological zones were selected. The results showed that T. parva infection status was different across the agroecological zones and was associated with feeding management. Calves raized in the lower altitude zones were at a higher risk of T. parva infection than those raised in higher altitude zones.